Situational awareness of pilots in the cruise : a thesis submitted as partial fulfilment of the requirements for the degree of Masters of Aviation at Massey University, Palmerston North, New Zealand - Vincent, Nicholas (Massey University, 2018)
Situational Awareness is a corner stone of flight safety; a flight crew or single pilot must be situationally aware to allow the flight to operate without incident and to detect any failure or faults as soon as practically possible. This gives pilots the greatest length of time to respond and then either resolve the issue, or minimize escalation. This research explores whether the implementation of a checklist is beneficial during a portion of the flight when there is low outside stimulation for the pilot. The research takes a practical approach, attempting to find not just an effect but a meaningful effect that could potentially improve safety in a real-world scenario. In accordance with this, Fisher’s significance testing is used, and while the results are statistically interpreted using this method, Bayes factors are also used in an attempt to provide a more relevant answer to the research’s endeavor to find a way to meaningfully increase flight safety.
Keywords: Air pilots -- Performance; Situational awareness -- Measurement; Aeronautics -- Safety measures